ILLICIT TRAFFICKING OF WEAPONS AND ARMS AS POSSIBLE SECURITY PROBLEM (Annual of the Faculty of Philosophy in Skopje, 2009)
The illicit production, transfer and spreading od small and light weapons and theirs excessive accumulation and uncontrolled broadening in many regions in the world, have broad range of humanitarian and social-economic consequences, illegal trafficking of small amis and light weapons represents serious threats for peace, reconciliation, security, stability and sustainable development on individual, national, regional and international level.This paper examines the dynamics and trends of illegal trafficking of small arms and light weapons, identifies the role of transnational organized crime, and considers the measures of control over illicit arms trafficking which governments, security agencies, and law enforcement agencies must take to combat this global security problem.
Keywords: ILLICIT TRADE OF SMALL AND LIGHT WEAPONS; SECURITY; TRANSNATIONAL ORGANIZED CRIME